Jamak Tanpa Safar: Solusi Alternatif Ibadah - Muhammad Habibul Amin; M. Iqbal Irhan (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This article aims to explain the permissibility of combining (jamak) two fard prayers without having to travel far (safar) due to rain, busyness, traffic jams, celebrations (walimah) as a form of convenience in worship. In this condition, jamak becomes an alternative solution for Muslims because of the difficulty of fulfilling the obligation to pray in the time specified in the Qur'an and hadith. As literature research, this article will examine the plural prayer in the perspective of scholars, such as Abdurrahman bin Muhammad Ba'lawi, Yusuf al-Qardhawi, and Alwi Ahmad Saqqaf who provide rukhshah (relief) solutions in worshiping Allah. This research is qualitative in nature, which is done by collecting, analyzing, and interpreting narratives comprehensively against visual data to get a full, comprehensive, and holistic insight into the phenomenon of plural prayers for other than travelers. The results of this study indicate that combining two prayers without traveling far is permissible because of busyness, traffic congestion, and celebrations (walimah). Associated with current conditions, the situation is a form of masyaqqah that cannot be avoided so as to perform plural prayers, both taqdim and ta`khir.